2012
DOI: 10.17265/2159-5542/2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Cheat Sheet or Open-Book? A Comparison of the Effects of Exam Types on Performance, Retention, and Anxiety

Abstract: The differences between open-book, cheat sheet, and closed-book exams were examined in two different types of psychology courses. A total of 297 students enrolled in eight sections of Introductory Psychology and 99 students This study developed from an ongoing debate in our department, one which is probably happening in many academic departments. The question is which type of exam is best. All teachers want their students to learn and retain the material they cover and at the same time enjoy the process of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…Therefore, it is being concluded that mean marks scored by the students in an OBE is significantly higher than the mean marks scored in a CBE. This is in line with the results of studies conducted in the past, showing that students score higher in an OBE (Agarwal et al, 2008;Francis, 1982;Gharib et al, 2012;Krarup et al, 1974). However, many researchers have also provided empirical evidence that there are no significant differences in the performance of the students (Brightwell et al, 2004;Ioannidou, 1997;Pauker, 1974).…”
Section: Empirical Results: Open Book Versus Close Booksupporting
confidence: 89%
“…Therefore, it is being concluded that mean marks scored by the students in an OBE is significantly higher than the mean marks scored in a CBE. This is in line with the results of studies conducted in the past, showing that students score higher in an OBE (Agarwal et al, 2008;Francis, 1982;Gharib et al, 2012;Krarup et al, 1974). However, many researchers have also provided empirical evidence that there are no significant differences in the performance of the students (Brightwell et al, 2004;Ioannidou, 1997;Pauker, 1974).…”
Section: Empirical Results: Open Book Versus Close Booksupporting
confidence: 89%
“…Different degrees of motivational effects might therefore explain the difference between our findings and earlier laboratory studies. The results of Gharib et al. (2012) field experiment in which open-book and closed-book tests in a university course did not affect performance in a later test might speak against this interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, final test delays of up to 1 week might have been too short to detect a retrieval practice effect compared to open-book testing. The study by Gharib et al. (2012) used a delay of 2 weeks but their findings are not easily comparable to the other studies, as the manipulation did not concern a learning condition in terms of a practice test but an exam condition: students had either access to their notes, to a self-prepared cheat sheet, or to none of the former in the exam.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations